STUDY OF COVID-19 CASE WITH MULTIPLE COMORBIDITIES: SEVERE TO SURVIVAL (Bioresearch Communications, 2022)
Elderly COVID-19 patients with comorbidities suffer from severe complications and mostly didn’t survive. We report management of a 80-year-old patient with several comorbidities. Due to the fast deterioration of the condition, physicians treated her with Tocilizumab along with medications for other underlying diseases. She recovered completely after therapy with Actemra.Bioresearch Commu. 9(1): 1177-1179, 2023 (January)